Peningkatan Kesehatan Mental dengan Pemantauan Kadar Vitamin D pada Kelompok Lanjut Usia - Anastasia Ratnawati Biromo; Alexander Halim Santoso; Noer Saelan Tadjudin; William Gilbert Satyanegara; Edwin Destra; Farell Christian Gunaidi; Alicia Herdiman; Frilliesa Averina (Universitas Muhammadiyah Manado, 2025)
Vitamin D is a micronutrient required by the body. Vitamin D has various functions, including its potential to prevent depression. There are studies suggesting that people with depression are at risk of vitamin D deficiency. This study discusses the correlation between vitamin D and depression. This is a cross-sectional study designed to investigate the relationship between vitamin D levels and depression in elderly (≥ 60 years) residing at Bina Bhakti Nursing Home. Participants who meet the criteria underwent measurement of vitamin D levels and assessment for depression using the Geriatric Depression Scale (GDS). Spearman correlation is used as the statistical analysis to evaluate the relationship between variables. 93 respondents met the criteria with average age of 74.19 years (61-97 years). 77 respondents were female (82.8%) and 16 respondents (17.2%) were male. The mean vitamin D level was 9.78 ng/ml (1.07-25.6ng/mL) and the mean GDS score was 4.51 (0-15). The results of the analysis showed a significant negative correlation between vitamin D levels and GDS scale (-0.287, p-value=0.005). Low vitamin D levels are associated with increased GDS scores, indicating that it is important for the elderly to fulfill their vitamin D needs as an preventive measure against depression